La Ejecución inmediata de las Pruebas Científicas de Drogodependencia en los casos de Delitos Flagrantes de la tenencia de Sustancias Estupefacientes y Psicotrópicas - Herrera Álvarez, Joselyne Abigail (2016)
This paper discusses legal research: "The Immediate Execution of the Scientific Evidence of Drug Dependence in the Cases of Flagrant Offenses of the Holding of Narcotic and Psychotropic Substances."The penal system trying to solve the problem of traffic and consumption of narcotic and psychotropic substances, has developed policies and laws that guarantee the effective protection of citizens' rights, but at the moment of applying the sanction when it is a blatant crime for the Possession of substances subject to control arises a greater problem, since when a person is apprehended in flagrante delicto by the possession of these substances there is inefficacy on the part of the judicial operators when verifying the functional organic situation of the individual apprehended through the Recognition test of drug addict. As this test is not immediately practiced, the procedure is hindered, since it may be the case that the apprehended individual is a trafficker and when not done immediately this test is being given time to consume the substances and change their situation Organic and therefore their legal status; Or it may be the case that it is an addict subject and not to perform the test of recognition of drug addict is criminalizing conduct that is not punishable, since the Constitution recognizes addictions as a public health problem.